A New Measure of Interpersonal Exploitativeness - Brunell, Amy B.; Davis, Mark; Schley, Dan R.; Eng, Abbey; van Dulmen, Manfred; Wester, Kelly; Flannery, Daniel (Frontiers in Psychology, 2013)
Measures of exploitativeness evidence problems with validity and reliability. The present set of studies assessed a new measure (the Interpersonal Exploitativeness Scale) that defines exploitativeness in terms of reciprocity. In Studies 1 and 2, 33 items were administered to participants. Exploratory and Confirmatory Factor Analysis demonstrated that a single factor consisting of six items adequately assess interpersonal exploitativeness. Study 3 results revealed that the Interpersonal Exploitativeness Scale was positively associated with “normal” narcissism, pathological narcissism, psychological entitlement, and negative reciprocity and negatively correlated with positive reciprocity. In Study 4, participants competed in a commons dilemma. Those who scored higher on the Interpersonal Exploitativeness Scale were more likely to harvest a greater share of resources over time, even while controlling for other relevant variables, such as entitlement. Together, these studies show the Interpersonal Exploitativeness Scale to be a valid and reliable measure of interpersonal exploitativeness. The authors discuss the implications of these studies.